Diagnostic Value of Urinary CD80 in Typical and Atypical Nephrotic Syndrome - Hossain, Md Shorab; quader, Mohammed Maruf ul; Biswas, Susmita; Chowdhury, Muhammad Jabed Bin Amin; Haque, Salina; Chowdhury, Dhiman; Mia, Mohammad Musa; Hadi, Fuad Md Abdul; Amin, Md Fakhrul; Islam, Mohammad Toufiqul (Bangladesh Journal of Child Health, 2024)
Background: Cluster of differentiation 80 is one of the important biomarker which is present on podocytes. Urinary CD80 concentration increases only in patients with typical nephrotic syndrome in active state and level remains normal in patients with atypical nephrotic syndrome. Objective: To evaluate urinary CD80 concentration as a diagnostic marker of typical and atypical nephrotic syndrome. Methods: This was a cross sectional study, performed in the Department of Paediatrics & Paediatric Nephrology, Chittagong Medical College Hospital, Chattogram. Thirty nine with typical and 36 with atypical nephrotic syndrome were enrolled from January 2020 to July 2021.Urinary CD80 concentration was measured and compared between typical and atypical nephrotic syndrome. Results: Mean urinary CD80 concentration in typical nephrotic syndrome (671.92 ±328.45) was found significantly higher (p<0.001) than atypical nephrotic syndrome patients (122.30 ±158.47). The area under the curve for typical nephrotic syndrome was 0.946 for urinary CD80 concentration (95% confidence interval: 0.899–0.992) (p<0.001). Urinary CD80 concentration 114.9 ng/g of creatinine was found most appropriate cut-off value with the sensitivity 92.3% and the specificity 27.8% for the differentiation of typical (active state) and atypical nephrotic syndrome. Conclusion: Urinary CD80 level found significantly higher in patients with typical nephrotic syndrome than atypical nephrotic syndrome. Along with the other diagnostic criteria, urinary CD80 may be used as a non-invasive biomarker to differentiate typical and atypical nephrotic syndrome. Bangladesh J Child Health 2023; Vol 47 (2) : 78-83